2020
DOI: 10.1177/1751143720978849
|View full text |Cite
|
Sign up to set email alerts
|

The patient with cirrhosis in the intensive care unit and the management of acute-on-chronic liver failure

Abstract: Acute on chronic liver failure (ACLF) is a clinical syndrome characterised by acute hepatic decompensation, multi-organ failure and high mortality, in patients with cirrhosis.  Organ dysfunction in ACLF is often reversible and when necessary these patients should be considered appropriate candidates for admission to an intensive care unit (ICU). The yearly increase in numbers of patients with ACLF admitted to ICU has been matched with an improvement in survival.  ACLF has only been recently defined. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(155 reference statements)
0
3
1
Order By: Relevance
“…All subjects in our study underwent respiratory intubation and/or central venous catheter placement. Mortality in our study being on the lower end of previously reported rates despite our inclusion criteria suggests that outcomes are either improving or that previous conclusions were overly pessimistic [ 2 , 8 , 10 , 13 , 28 , 29 ]. Notably, we did include patients who received a liver transplant during the index hospitalizations (n = 400), which is another possible explanation for the relatively low mortality.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…All subjects in our study underwent respiratory intubation and/or central venous catheter placement. Mortality in our study being on the lower end of previously reported rates despite our inclusion criteria suggests that outcomes are either improving or that previous conclusions were overly pessimistic [ 2 , 8 , 10 , 13 , 28 , 29 ]. Notably, we did include patients who received a liver transplant during the index hospitalizations (n = 400), which is another possible explanation for the relatively low mortality.…”
Section: Discussioncontrasting
confidence: 58%
“…Reported ICU mortality rates for patients with cirrhosis have ranged from 29 to 87% [ 4 , 8 , 13 , 17 20 ]. While recent studies have suggested that outcomes in critical care for decompensated cirrhosis may be improving, the generalizability of available data is limited by differences in studied populations and institutions along with low sample sizes and overall outcomes in the U.S. are still unclear [ 2 , 13 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cirrhosis etiologies included chronic alcohol (ETOH) associated liver disease, non-alcoholic steatohepatitis (NASH), Hepatitis C (HCV), cholestatic liver disease (primary sclerosing cholangitis, primary biliary cirrhosis), inherited/genetic disease (hereditary hemochromatosis, alpha-1 anti-trypsin deficiency), and cryptogenic/other. Clinical decompensations included hepatic encephalopathy, jaundice, ascites, hepato-renal syndrome, spontaneous bacterial peritonitis (SBP), and variceal bleed[ 2 , 11 ]. Patients were considered to have a cardiac diagnosis if their past medical history included diagnosis or treatment of a cardiac arrhythmia, coronary artery disease, or cardiomyopathy with heart failure.…”
Section: Methodsmentioning
confidence: 99%
“…6 FIs can precipitate acute-on-chronic liver failure (ACLF) multi-organ failures and often leads to delisting from liver transplantation. 10 A robust innate immune function is essential to combat fungal pathogens from breaching the natural barriers and causing infection. Impaired immunity, possibly due to ineffective phagocytosis and defective Tcell cytotoxicity, puts patients with cirrhosis at a high risk of FIs.…”
Section: Introductionmentioning
confidence: 99%
“…FIs are associated with increased morbidity due to acute kidney injury, hepatic encephalopathy, gastrointestinal bleeding and shock 6 . FIs can precipitate acute‐on‐chronic liver failure (ACLF) multi‐organ failures and often leads to delisting from liver transplantation 10 . A robust innate immune function is essential to combat fungal pathogens from breaching the natural barriers and causing infection.…”
Section: Introductionmentioning
confidence: 99%